Pembinaan Desa Wisata Sehat Gabugan dengan melibatkan mahasiswa interprofesi dalam melatih kader Program Indonesia Sehat – Pendekatan Keluarga (PIS-PK) - Widyandana Widyandana; Tutik Kusdaryanti; Dimas Septian Eko Wahyu Sumunar; Dianing Pratiwi; Fitriana Fitriana; Nandyan Sulaksana Nugraha; Vita Yanti Anggreni; Gandes Retno Rahayu (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
The Government of Republic of Indonesia launched Healthy Indonesia Program with Family-Centered Approach (PIS-PK). This program intended to improve public health in commons beneath the management of public health care. However, it remains challenging for public health care to reach all families in the working area. Active participation from volunteers or cadres to encourage the implementation of this program is required. Gabugan Tourism Village is an educational tourism village in a vision to develop the concept of